An exceptionally stable luminescent cadmium() metal-organic framework as a dual-functional chemosensor for detecting Cr() anions and nitro-containing antibiotics in aqueous media - Fan, Liming; Zhao, Dongsheng; Li, Bei; Chen, Xi; Wang, Feng; Deng, Yuxin; Niu, Yulan; Zhang, Xiutang (CrystEngComm, 2021)
Based on four kinds of binuclear cadmium-carboxyl SBUs and two independent cadmium cations, a robust metal-organic framework, with the formula {[Cd 10 (DDB) 4 (bpz) 8 (DMA)(H 2 O) 8.2 ]·2H 2 O} n ( 1 ), was successfully fabricated under solvothermal conditions. Benefitting from the excellent moisture susceptibility as well as luminescence property, 1 exhibits highly sensitive detectability as a dual-response chemosensor for Cr( vi ) anions and broad-spectrum nitro-containing antibiotics in aqueous media through luminescence quenching, with excellent recyclability and low detection limits. Moreover, the fluorescence recognition mechanisms were explored from both internal filter effect (IFE) and photo-induced electron transfer (PET) viewpoints. Based on four kinds of SBUs, a robust Cd( ii ) LMOF was fabricated that possessed highly sensitive detectability as a dual-response chemosensor for Cr( vi ) anions and broad-spectrum nitro-containing antibiotics in aqueous media.